The influence of annealing temperature on the compressive deformation and damage behavior of ultrafine grained iron. (March 2021) - Li, X.H.; Jiang, Q.W.; Li, M.; Yang, P.; Xiong, J.S.; Zhao, Z.C.; Zhang, S.
Abstract: Commercially pure iron (CP Fe) was manufactured by equal channel angular pressing (ECAP) to explore the effects of annealing temperature on the deformation behavior of the materials with BCC structure. The effect of annealing temperature on the room-temperature (RT) compressive deformation behavior, sub-structures, and surface damage characteristics of the ECAP Fe were systematically studied. The results showed that as the annealing temperature increased, grain size of the ECAP Fe significantly increased, the dislocation density decreased, the grain boundaries were clear, and the grain structure was composed of equiaxed grains and sub-grains. When the ECAP Fe was annealed at temperatures below 673 K, the strength and flow stability under uniaxial compression were significantly improved. Better uniform deformation ability and grain boundary coordinated deformation ability were shown with only small-scale shearing on the compression surface. Secondary shear lines with a cross-distribution and a small amount of discontinuous fine micro-shear cracks appeared near the micro-shear bands, but large-scale shear bands were not observed in the compressed annealed samples. When annealed above 673 K, the strength and flow stress promptly decreased, and a long strain hardening stage occurred. Large-scale shear cracks appeared on the compressed surface, which was seriously damaged. The deformation mechanisms under different annealing effects are further discussed. Use of appropriate annealing temperature is necessary to improve the coordinated deformation of the grain boundaries. Additionally, the mechanical properties of the material will also diminish the damage level.